2016
DOI: 10.3354/meps11823
|View full text |Cite
|
Sign up to set email alerts
|

Loggerhead turtles killed by vessel and fishery interaction in Virginia, USA, are healthy prior to death

Abstract: Human-induced mortality of marine animals is a complex issue and the health of animals prior to human interaction is often questioned. We reviewed 74 cases of loggerhead turtles in the mid-Atlantic region of the US to determine whether fresh, dead loggerhead turtles that died from acute vessel or fishery interaction (acute VI/FI) were healthy animals prior to human-induced mortality. We used the presence of significant underlying pathology to determine health status and compared the body condition and adipose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…All the loggerhead turtles examined were in good body condition; this was also confirmed by modified Fulton's K values. Barco et al found a positive correlation between modified Fulton's K values and the adipose mass index, giving reasons for the significantly higher PCB levels in adipose tissue than in muscle tissue found in the present study.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…All the loggerhead turtles examined were in good body condition; this was also confirmed by modified Fulton's K values. Barco et al found a positive correlation between modified Fulton's K values and the adipose mass index, giving reasons for the significantly higher PCB levels in adipose tissue than in muscle tissue found in the present study.…”
Section: Discussionsupporting
confidence: 56%
“…All loggerhead sea turtles examined belonged to the thin and normal classes, according to Heithaus et al [22] and Barco et al [23], with a convex underside and substantial fat reserves near the neck.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…At the same time, it may also reflect the animals' health condition, a different lipid composition or the complexity behind the distribution and fate of pollutants in the body of a species for which metabolic capacities and toxicokinetics in general are poorly known. Barco et al (2016) observed that the amount of lipids in fat tissue differed between turtles who died either from fishing incidents or other causes, indicating that those who died through the former cause were in better condition with higher lipid amounts. In the present study, the causes of death could not be identified for all individuals, however, the majority of individuals had infections, serious flesh wounds or considerable quantities of plastic debris in their stomachs.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, working with stranded animals has been suggested to lead to biases (Casale et al, 2016). Surveying plastics in animals that die from fisheries interactions, however, might be more likely to exhibit normal healthy body condition than those that die of other causes (Barco et al, 2016;Casale et al, 2016). Consequently, longline bycaught turtles used in this study provide a unique data source to assess the plastic burden in what may be relatively healthy individuals.…”
Section: Plastic Ingestion In Post-hatchling Marine Turtlesmentioning
confidence: 99%